Reforma ultramontana e il tanto vantato cattolicismo del Sul de Minas : os Carmelitas Descalços na Diocese de Pouso Alegre-MG (1911-1922) - Silva, Rafaela Ferreira da (2015)
The present dissertation studies the process of ultramontane reform of the Brazilian Catholicism through the acting of the Discalced Carmelites of the Roman Province in the South of Minas Gerais State, specifically in the parishes of Cambui and Córrego do Bom Jesus, both belonging to the Diocese of Pouso Alegre, in the period from 1911 until 1922. The cutout temporal adopted is justified by the foundation of this mission in Córrego do Bom Jesus and Cambui in 1911 and goes until 1922 when the house of Cambuí is closed and the teresianos left the south of the Minas Gerais State. In this period of more than a decade, several interventions of the Discalced Carmelites are realized in these two communities and they are associated with the attempt of introduction of the directives of the ultramontane reform of the Church in Brazil, taking the present reformative project as a base in the new Diocese of PousoAlegre. Inserted in this new configuration of the Brazilian Catholicism, the teresianos will devote themselves the attempt of gradual substitution of a not much austere, festive, social, familiar religious practice and in a large extent lay for the Roman and reformed Catholicism which emphasis falls back on the sacraments. We intend to study the presence of the teresianos in these parishes considering as the relations between the imposed forms of the ultramontane Catholicism and the identities always reaffirmed by the present laymen in the rites and experts of the local religiosity. The main used fountains were extracted of the illustrated magazine of the Order of the Discalced Carmelites, Il Carmelo, of the book of conservation of these parishes, of the manuscript Appunti Storici della nostra missione nel Brasile, of the catholic newspaper Tribuna Sul Mineira, of the Collective Pastorals of 1911 and 1915, the book Actas y Decretos del Concilio Plenario de la América Latina and other documents found in the Archdiocese of Pouso Alegre, in the archive of the Province São José of the Discalced Carmelites (at São Paulo), in the Curia Generalizia of the Order and in the archive of the Roman Province, both in Rome. We point that this reformative project begun before the arrival of the Order, prepared series of interventions with the objective to control and to discipline the local cultural practices considered profane that intensified in the period comprised by the current inquiry, project that stayed far from achieving all its goals